2021
DOI: 10.33448/rsd-v10i10.18488
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores para a ocorrência da dengue em municípios do oeste de Santa Catarina, Brasil

Abstract: A dengue tem sido uma preocupação constante na área da saúde pelas características endêmicas e virais da doença tornando-a um problema de saúde pública. Este estudo teve como objetivo descrever indicadores para a ocorrência da dengue em municípios da região Oeste de Santa Catarina. Trata-se de uma pesquisa quantitativa de caráter descritivo-transversal. A investigação ocorreu no segundo semestre de 2017 em quatro municípios (Chapecó, Descanso, Pinhalzinho e São Miguel do Oeste), que apresentaram os maiores índ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Dengue is influenced by season, local rainfall, poor housing conditions and poor sanitation, aspects relevant to the neighbourhoods of the studied population (Skalinski et al, 2019). Furthermore, Brazilian studies (Morschbacher et al, 2021) have demonstrated that a high incidence of dengue is related to regions with low HDI levels. The number of FHTs in school districts was positively associated with SRH, even after other variables were included in the models (see Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Dengue is influenced by season, local rainfall, poor housing conditions and poor sanitation, aspects relevant to the neighbourhoods of the studied population (Skalinski et al, 2019). Furthermore, Brazilian studies (Morschbacher et al, 2021) have demonstrated that a high incidence of dengue is related to regions with low HDI levels. The number of FHTs in school districts was positively associated with SRH, even after other variables were included in the models (see Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Estudos também mostram a importância de avaliar as ações e serviços de saúde pela AB e ESF (MORSCHBACHER et al, 2021). Nesse aspecto, a qualidade e a cobertura de dados de saúde são refletidas sobre as condições socioeconômicas de uma população e, assim, podem se transformar em indicadores de saúde, como ocorre com os casos de dengue na região do Estado do Pará, analisados através das comparações de mudanças dos números de casos da doença com determinantes da saúde ao longo do tempo (MACINKO; MENDONÇA, 2018).…”
Section: A B D Cunclassified